Trans-sulfuration Pathway Seleno-amino Acids Are Mediators of Selenomethionine Toxicity in Saccharomyces cerevisiae* - Lazard, Myriam (J Biol Chem, 2015)
Toxicity of selenomethionine, an organic derivative of selenium widely used as supplement in human diets, was studied in the model organism Saccharomyces cerevisiae. Several DNA repair-deficient strains hypersensitive to selenide displayed wild-type growth rate properties in the presence of selenomethionine indicating that selenide and selenomethionine exert their toxicity via distinct mechanisms. Cytotoxicity of selenomethionine decreased when the extracellular concentration of methionine or S-adenosylmethionine was increased. This protection resulted from competition between the S- and Se-compounds along the downstream metabolic pathways inside the cell. By comparing the sensitivity to selenomethionine of mutants impaired in the sulfur amino acid pathway, we excluded a toxic effect of Se-adenosylmethionine, Se-adenosylhomocysteine, or of any compound in the methionine salvage pathway. Instead, we found that selenomethionine toxicity is mediated by the trans-sulfuration pathway amino acids selenohomocysteine and/or selenocysteine. Involvement of superoxide radicals in selenomethionine toxicity in vivo is suggested by the hypersensitivity of a Δsod1 mutant strain, increased resistance afforded by the superoxide scavenger manganese, and inactivation of aconitase. In parallel, we showed that, in vitro, the complete oxidation of the selenol function of selenocysteine or selenohomocysteine by dioxygen is achieved within a few minutes at neutral pH and produces superoxide radicals. These results establish a link between superoxide production and trans-sulfuration pathway seleno-amino acids and emphasize the importance of the selenol function in the mechanism of organic selenium toxicity.